Pengembangan Kapasitas Nelayan Tangkap Gillnet Di Dusun Talaga Nipa, Kabupaten Seram Bagian Barat: Pengembangan Kapasitas Nelayan Tangkap Gillnet Di Dusun Talaga Nipa, Kabupaten Seram Bagian Barat - Haruna Haruna; Ruslan H.S. Tawari; Selfi Sangadji (Buletin SWIMP, 2022)
This service activity aims to provide understanding and knowledge to bottom gill net fishermen on technical, bio-ecological, and sustainable fisheries management aspects in Talaga Nipa Hamlet, West Seram Regency. The activity procedure applies experimental fishing methods to three mesh sizes 1.75 inch, 2.0 inch, 2.25 inch 3 inch. The construction and operation of fishing gear is carried out together with fishermen. The composition of gill net catches consisted of 7 species. Distribution size of the sample fish is mackerel (Rasterlliger kanagurta) at a size of 21.5-31.5 cm, and the dominant size of the 2.0-inch mesh is 24.5 cm, while the 2.25 and 2.5-inch meshes are 25, 5 cm. The optimum proportion caught in 2.0 inch mesh is 23.35 cm, 2.25 inch mesh is 26.27 cm, and 2.5 inch mesh is 27.62 cm. The discussion and sharing stages of the results of this analysis show that fishermen have understood the sustainability of fishery resources, which are technically related to fishing gear, bio-ecology, and management management. The results of this activity are expected to become knowledge so that the sustainability of fisheries resources in coastal areas is optimal.